1996
DOI: 10.1007/bf00439230
|View full text |Cite
|
Sign up to set email alerts
|

The Internet: A modern Pandora's Box?

Abstract: Two different views of the Internet are presented. One is from the perspective of an author who has written a personal account of her own breast cancer experience, while the other is from the perspective of a cancer researcher who is interested in quality of life research. The article is written in a format that reflects the somewhat informal style of messages sent to Internet discussion groups. For better or worse, the Internet has arrived as a force in our lives, and medical information and support constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Some applaud this shift as an opportunity for partnerships in health care (Thomas, 1998) and greater use of the consumer as a resource (Wilkins, 1999), while others see a Pandora's box of 'unmanageable problems' [(Mayer and Till, 1996), p. 568]. Many providers are threatened by their loss of power and fear damage to physician-patient communication (Anonymous, 2000).…”
Section: Collaborations or Collisions Ahead? Implications For The Heamentioning
confidence: 99%
“…Some applaud this shift as an opportunity for partnerships in health care (Thomas, 1998) and greater use of the consumer as a resource (Wilkins, 1999), while others see a Pandora's box of 'unmanageable problems' [(Mayer and Till, 1996), p. 568]. Many providers are threatened by their loss of power and fear damage to physician-patient communication (Anonymous, 2000).…”
Section: Collaborations or Collisions Ahead? Implications For The Heamentioning
confidence: 99%
“…Only a few studies of web-based breast cancer support groups have been reported [12,14-19]. One of these studies, by Klemm et al [17], involved line-by-line analysis of postings on prostate, breast, and mixed internet-based cancer support groups.…”
Section: Discussionmentioning
confidence: 99%
“…The BCML was established in early 1994, and has operated continuously since that time [23,14]. It's an unmoderated English-speaking online (via email) discussion group, based at Memorial University of Newfoundland in St. Johns, Newfoundland, Canada.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some researchers, the Web is a “Pandora’s Box” that has both benefits and costs [17, 18], particularly its impact on health-seeking knowledge. In a Pew Research poll from 2013 [19], a majority of those surveyed (73%) sought health-related information with a third of those (35%) diagnosing themselves as opposed to seeing a doctor.…”
Section: Introductionmentioning
confidence: 99%